2020
DOI: 10.1002/jgm.3202
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA HOXC‐AS1 promotes gastric cancer via binding eIF4AIII by activating Wnt/β‐catenin signaling

Abstract: Background Long non‐coding RNAs (lncRNAs) function as oncogenes or tumor suppressor genes in several cancers. The present study aimed to determine the functions of lncRNA HOXC‐AS1 in gastric cancer (GC) in vitro. Methods A quantitative reverse transcriptase‐polymerase chain reaction (qRT‐PCR) was used to measure the expression of lncRNA HOXC‐AS1 in GC cell lines and normal cells. After silencing HOXC‐AS1 in GC cells, a cell counting kit‐8 assay monitored the viability of the cells. qRT‐PCR and western blot doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Zhou et al reported that the long noncoding RNA (lncRNA), HOXC-AS1, inhibits GC cell apoptosis by binding eIF4A3 in the Wnt/β-catenin signaling pathway (Zhou et al, 2020). Another study has revealed that eIF4A3 may bind the circular RNA, PVRL3 (Sun et al, 2018).…”
Section: Expression Patterns Of Eif4a3 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al reported that the long noncoding RNA (lncRNA), HOXC-AS1, inhibits GC cell apoptosis by binding eIF4A3 in the Wnt/β-catenin signaling pathway (Zhou et al, 2020). Another study has revealed that eIF4A3 may bind the circular RNA, PVRL3 (Sun et al, 2018).…”
Section: Expression Patterns Of Eif4a3 In Cancersmentioning
confidence: 99%
“…In hepatocellular carcinoma, loss-of-function assays have shown that the silencing of eIF4A3 inhibits cell proliferation, migration, and EMT (Zhang et al, 2020). In GC tissues, eIF4A3 is downregulated compared to adjacent normal tissues, and the silencing of eIF4A3 increases lncRNA HOXC-AS1 expression, which promotes GC cell proliferation and EMT but represses apoptosis (Zhou et al, 2020). In cervical cancer, Sui et al reported that hsa_circ_0101119 promotes cell proliferation, migration, and invasion but suppresses apoptosis in cervical cancer via an interaction with eIF4A3 to inhibit TCEAL6 expression (Sui et al, 2021).…”
Section: Biological Functions Of Eif4a Protein In Cancermentioning
confidence: 99%
“…In this study, some of the irlncRNAs in the process of modeling that have been already identi ed play an important role in malignant phenotypes of various cancer types, such as LINC01063 [24,25], HOXC-AS1 [26,27], LINC02454 [28,29] and SCAT1 [30]. Furthermore, previous reports have shown that LINC00460 [31], C5orf66-AS1 [32] and TMPO-AS1 [33] are associated with prognosis and treatment outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 75%
“…So far, a number of evidence show that lncRNAs are involved in tumor progression and cisplatin resistance of gastric cancer via various mechanisms. [25][26][27][28] NUTM2A-AS1 has not been studied in cancer, including gastric cancer. Our group, for the first time, prove that NUTM2A-AS1 accelerates tumor invasion, angiogenesis, and cisplatin resistance at cellular and animal level.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a number of evidence show that lncRNAs are involved in tumor progression and cisplatin resistance of gastric cancer via various mechanisms 25‐28 . NUTM2A‐AS1 has not been studied in cancer, including gastric cancer.…”
Section: Discussionmentioning
confidence: 99%